2008
DOI: 10.1007/s11262-008-0212-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and phylogenetic analysis of the large (L) segment of the Tahyna virus genome

Abstract: The Tahyna virus (TAHV) is an important human pathogen in the Bunyaviridae family. To date, only the S and M segments of this virus have been sequenced, but the sequence of the L segment hasn't been established yet. In this study, we sequenced 963 nucleotides of the L segment of TAHV, comprising pre-motif A and motif A in region 3 of the RNA polymerase gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…The tree showed that the Tospovirus clade was closer to the Orthobunyavirus genus, followed by the Hantavirus and Nairovirus genera, similar to the findings by Roberts et al [40] when analyzing the La Crosse L segment. The general topology of this tree based on the complete L sequences is also very similar to that obtained when only partial L sequences were used for phylogenetic analysis [41].…”
Section: Discussionsupporting
confidence: 63%
“…The tree showed that the Tospovirus clade was closer to the Orthobunyavirus genus, followed by the Hantavirus and Nairovirus genera, similar to the findings by Roberts et al [40] when analyzing the La Crosse L segment. The general topology of this tree based on the complete L sequences is also very similar to that obtained when only partial L sequences were used for phylogenetic analysis [41].…”
Section: Discussionsupporting
confidence: 63%
“…The BUNV L protein is 259 kDa and contains 2238 aa (Elliott, 1989). Although no extended homology is found with other negative-stranded virus polymerases or even with the polymerases of viruses in other genera in the family Bunyaviridae , the motifs conserved in other RdRps that comprise the ‘polymerase module’ have been identified (Aquino et al , 2003; Elliott, 1989; Gowda et al , 1998; Muller et al , 1994; Poch et al , 1989; Quinan et al , 2008; Roberts et al , 1995; van Poelwijk et al , 1997). Its role as the viral polymerase was confirmed by the ability of the L protein to transcribe authentic BUNV RNP templates (Jin & Elliott, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…4). Despite this difference in length and sequence, nairovirus L proteins still show the four conserved functional regions previously described for other bunyavirus L proteins [94,108,131,139,177]. The bunyavirus L proteins contain the RNA-dependent RNA polymerase (RdRp), and the most conserved region of the L segment among nairoviruses is the region corresponding to the coding sequence for the core catalytic domains of the RdRp [8,85,108].…”
Section: The L Proteinmentioning
confidence: 97%
“…Nairoviruses share many of their features with other bunyaviruses, e.g., replication in the cytoplasm, budding in the Golgi, and their coding and RNA replication strategy. From phylogenetic studies, the members of the genus Nairovirus appear to be most closely related to those of the genus Phlebovirus of all bunyaviruses [108,131,139,177]. However, nairoviruses possess many features not found in other bunyaviruses.…”
Section: Final Remarksmentioning
confidence: 99%